(untitled) (Current Horticulture, 2024)
Tropical tuber crops are mainly grown in limited scales even in the areas where they are consumed as staple foods. Due to change in the feeding habits tuber crops are gradually disappearing from the human diet. There is a necessary to promote the tuber crops cultivation by realizing their nutritional value and adaptability to harsh weather conditions. Chinese potato is one of the important minor tuber crops of nutritional and commercial value in tropical regions of the world. Chinese potato (Plectranthus rotundifolius) belongs to the family Lamiaceae (Labiatae) of order Lamiales with a chromosome number of 2n= 64. It has several medicinal properties due to the presence of flavanoids that help to lower the cholesterol level of blood. It is facing several production problems like photosensitivity, low yield and poor tuberization. Moreover, very less genetic variation is available in the country. As germplasm serves as an invaluable source of variation, there is a necessity to collect, conserve and make utilisation of it.